Differences in Prevalence of Metabolic Syndrome by Breastfeeding Experience of Women in Their 30s and 40s - Hye-Jin Kim, MSN, RN; Hee-Seung Kim, PhD, RN (Elsevier, 2016)
Purpose: The purpose of this study was to assess the differences in the prevalence of metabolic syndrome in women in their 30s and 40s by breastfeeding experience, using the the fifth Korea National Health and Nutrition Examination Survey (2010) data. Methods: In this cross-sectional study, a total of 1,053 healthy women in their 30s and 40s, who had given birth was analyzed. To compare women with and without breastfeeding experience, chi-square test and t test were used. The relationship between metabolic syndrome and breastfeeding was assessed using logistic regression analysis adjusted demographic and lifestyle covariates. Results: The breastfeeding experience of women in their 30s was associated with a decreased risk of elevated triglyceride after controlling for income, education, exercise and the last childbirth age [odds ratio (OR) = 0.44, 95% confidence interval (CI) (0.21, 0.95)]. In addition, women who breastfed more children had high odds of metabolic syndrome [OR = 4.03, 95%CI (2.03, 8.00)], and components of metabolic syndrome [abdominal obesity: OR = 2.02, 95%CI (1.17, 3.51), elevated triglyceride: OR = 1.98, 95%CI (1.14, 3.45), elevated blood pressure: OR = 2.65, 95%CI (1.28, 5.49)] than those who never breastfed children. Conclusions: This study found that postpartum breastfeeding may play a significant role in reducing the risk of metabolic syndrome and also that childbearing is associated with a higher incidence of metabolic syndrome among women in their 30s. For women in their 40s, the risk of metabolic syndrome did not significantly differ depending on the breastfeeding experience. This study indicated that breastfeeding can be a way to reduce metabolic health burdens in women in their 30s.